Impact of Aging on Sperm Quality of Sentul Roosters - Nining Haryuni; Hartutik Hartutik; Eko Widodo; Y A Tribudi; Sri Wahjuningsih (Indonesian Center for Animal Research and Development (ICARD), 2022)
This study was done to determine impact of aging on sperm quality of Sentul roosters. Materials used in this study were Sentul males aged 48, 58, 68 and 78 weeks, NaCl, eosin and aquades. Semen was collected by abdominal massage method. Completely randomized design (CRD) was applied in this study with 4 treatments in 5 repetitions. Statistical analysis showed that increasing age of rooster had a very significant effect (p0.01) on decreasing semen consistency, mass motility, spermatozoa concentration and increasing spermatozoa motility. Aging in Sentul roosters affected semen volume significantly (P0.05) but did not significantly affect (p0.05): semen pH, live spermatozoa, and spermatozoa abnormalities. Average volume of semen produced in this study ranged from 0.54-0.88ml; semen pH 6.80-7.12; mass movement score 1.60-3.00; spermatozoa concentration 2.76-4.86 x109/ml; spermatozoa motility 66-79%; Live spermatozoa 91.75-93.10%, and spermatozoa abnormalities 1.75-2.51%. Semen from Sentul males aged 48-68 weeks had a thick consistency and cloudy white in color. At the age of 78 weeks, the consistency varies from thick, medium and liquid. The color of semen in Sentul males aged 78 weeks also varied from clear white to cream. It is concluded that aging in Sentul roosters causes reproductive disorders which are characterized by low sperm quality. The best quality spermatozoa were produced by Sentul roosters aged 58-68 weeks.